TINDAKAN HUKUM TERHADAP ANGGOTA DPR-RI KARENA TERLIBAT KASUS KORUPSI - Siburian, Sukses M P; Sunarto, Atika; Aisyah, Aisyah (Hukum Universitas Sari Mutiara Indonesia, 2021)
The legal arrangements of DPR-RI members involved in corruption cases are regulated in Law Number 27 Year 2009 concerning the People's Consultative Assembly, the People's Legislative Assembly, the Regional Representatives Council, and the Regional House of Representatives and the Regulation of the People's Legislative Assembly of the Republic of Indonesia Number 1 / Dpr Ri / Year 2009 on the Code of Conduct which explains that every DPR-RI member who is proven to commit a criminal act of corruption will be dismissed from his membership as a member of DPR. The legal process of dismissing members of the DPR-RI involved in corruption cases is arranged in such a way from the start of the action of temporary dismissal until the dismissal remains. The legal process relating to the dismissal of DPR-RI members involved in corruption cases is known only in the form of interim termination and temporary dismissal, whereas in the interim change pattern is not known because the interchange pattern is not caused by the behavior of lawmakers who are contrary to the law but policy of political parties. The legal reason that a member of DPR-RI is dismissed in his / her position due to corruption case is caused by the member of DPR is proven to be corrupt and punished byimprisonment.